Intranasal Adhesion Formation in Post-Septoplasty Patients - SyedAliNaqi,MuhammadUsmanAhmad,MumtazAhmadUmar,JaisKarmani,TayyabHussain, SyedAliNaqi,MuhammadUsmanAhmad,MumtazAhmadUmar,JaisKarmani,TayyabHussain (Journal of Rawalpindi Medical College, 2018)
Background: To assess the role of intranasal splints and adhesion formation in post-septoplasty patients of deviated nasal septum(DNS). Methods: In this descriptive study patients (n=100), undergoing septoplasty for DNS were divided into two groups. In group A(n=50) patients intranasal splints were applied after septoplasty. In group B(n=50) patients no splints were applied. Plastic splints were used bilaterally. In group A, nasal splints were removed on 14th post-operative day. All patients in group A and B were followed to look for adhesion formation. Chi-square was used to compare the splinted and non-splinted groups. Results: There was difference in the frequency of nasal adhesion formation between the intranasal splinted patients (0%)and non-splinted (16%) which was statistically significant.(p value 0.006) Conclusion: The usage of intranasal splints in the septoplasty is very useful to prevent nasal adhesion formation